The Skin of Spectral Time in Grisey's Le Noir de l'Étoile. Issue 1 (26th April 2018) - EXARCHOS, DIMITRIS
Abstract: Following the aesthetics of pure continuity in the late 1970s, Grisey moved on to compose for unpitched percussion in Tempus ex Machina, focusing on pure rhythm. Shortly afterwards he elaborated on his theory of temporality in a talk and article of the same title; one decade later, he included Tempus as the first movement of Le Noir de l'Étoile . Grisey insisted on the significance of the perception of musical time, of the skin of time – as opposed to its skeleton or flesh . This article puts forward an interpretation of Grisey's thinking of temporality, drawing on concepts from French philosophy. It further provides an analysis of two sections of Le Noir, tracing these concepts in the structuring of musical time, with a view to providing a possible direction towards a re-definition of spectral time.